2007
DOI: 10.1007/s11244-007-0176-0
|View full text |Cite
|
Sign up to set email alerts
|

The NO x reduction mechanism by H2 under near isothermal conditions over Pt–Ba/Al2O3 Lean NO x Trap systems

Abstract: The study of the gas-phase NO reduction by H 2 and of the stability/reactivity of NO x stored over Pt-Ba/Al 2 O 3 Lean NO x Trap systems allowed to propose the occurrence of a reduction process of the stored nitrates occurring via to a Pt-catalyzed surface reaction which does not involve, as a preliminary step, the thermal decomposition of the adsorbed NO x species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…8, it can be concluded that first the consumption of the NO from the gas phase occurs and later reduction of surface nitrites/nitrates with ammonia. As was found previously, Pt must be involved in the reaction, because the reduction of stored nitrates/nitrites by NH 3 is not effective over Pt-free samples [54,60]. Moreover, this current study shows that when ammonia is a limiting agent, nitrates/nitrites remain on the catalyst surface unreacted, and at temperatures higher than 623 K decompose.…”
Section: Tpsr Over Catalyst With Preformed Nitrites/ Nitratessupporting
confidence: 57%
See 3 more Smart Citations
“…8, it can be concluded that first the consumption of the NO from the gas phase occurs and later reduction of surface nitrites/nitrates with ammonia. As was found previously, Pt must be involved in the reaction, because the reduction of stored nitrates/nitrites by NH 3 is not effective over Pt-free samples [54,60]. Moreover, this current study shows that when ammonia is a limiting agent, nitrates/nitrites remain on the catalyst surface unreacted, and at temperatures higher than 623 K decompose.…”
Section: Tpsr Over Catalyst With Preformed Nitrites/ Nitratessupporting
confidence: 57%
“…It has been reported that Ba addition to supported Pt catalysts results in an increase in NO x reduction activity in the absence of O 2 [19,52,53]. It was suggested that according to reactions (4)- (6), the presence of the alkaline or alkaline-earth metal ion weakens the N-O bond [54]. This will favor dissociation and subsequent reduction.…”
Section: Nh 3 Versus H 2 Reduction Of Nitrites/nitratesmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, the regeneration of model Pt-Ba/Al 2 O 3 Lean NOx Trap systems was also investigated. 18,[25][26][27][28][29][30] In this review the results obtained in our studies of the reduction phase will be reported, along with new data recently collected which better explain the chemistry involved in the reduction by H 2 of the stored NO x . NO (1000 ppm) was admitted to the reactor at t ¼ 0 s under He + O 2 (3% v/v) flow; after 100 s NO breakthrough was observed, while NO 2 evolution was seen starting from 200 s. Both the NO and NO 2 outlet concentrations increased with time until the NO feed flow was switched off (t ¼ 600 s).…”
Section: A Introductionmentioning
confidence: 99%